Evans Syndrome: A case report - F. Porcaro; M. Valenzise; G. Candela; F. Chiera; D. Corica; E. Pitrolo; S. Santucci; M. Romeo; S. Nigro; G. Zirilli (PAGEPress Publications, 2014)
We describe a case of a 14-years old caucasian female affected by autoimmune hemolytic anemia and thrombocytopenia successfully treated with intravenous immunoglobulin and steroids. Nevertheless, neutropenia occurred during follow-up period. Positivity of direct antiglobulin test and sieric anti-neutrophil antibodies suggested the diagnosis of Evans syndrome trilineage.